Hole-Filling for DIBR Based on Depth and Gradient Information. (18th February 2015) - Wang, Dan; Zhao, Yan; Wang, Zheng; Chen, Hexin
Depth image-based rendering (DIBR) is a method for generating new virtual images from known viewpoints. However, holes often appear in the rendered virtual images due to occlusion and inaccurate depth information. In this paper, we present a novel hole-filling algorithm to improve the image quality of DIBR. In the proposed method, depth information is added to the priority calculation function when determining the order of hole-filling. Then, the gradient information is used as auxiliary information when searching for the optimal matching block. Experimental results show that the proposed algorithm achieves better objective quality and also improves the subjective quality of the rendered images.